Perceived Value and Product Performance: A Case Study of Red Palm Oil Production in Malaysia - Shah Headan, Ayoob Hussain Shah (2023)
Palm oil has dominated trade in Malaysia's agricultural sector since 1990. However, consumer lacks awareness of red palm oil product quality and the real value possibly obtained from its consumption. Hence, the aim of this study is to assess the current consumer perceived value of red palm oil products. In addition, the objective of this study is to conduct a value analysis of red palm oil from the producers’ perspective and identify potential improvements for red palm oil production. This study applies a mixed-method research approach in which consumers’ opinions are assessed using a quantitative method while a qualitative approach is adopted to gain a deeper understanding of industry players' insights on palm oil product performance. Survey questionnaire is used to obtain opinions from palm oil consumers, while semi-structured interviews are conducted to gain deeper insights of red palm oil value analysis from palm oil producers. Descriptive statistics are applied to analyse the quantitative data and thematic analysis is used to obtain the patterns of input from qualitative data. The results found that red palm oil has great potential in the market if the awareness of the product is enhanced through promotion, and the price offered is reasonable. Production cost, consumer expectation of affordable price, sustainability requirements are among the key features of perceived value form the producers’ perspective. Additionally, the imperatives of government support, pro-active promotion and campaigns, and collaboration with strategic partners are proposed. This study contributes to practice by emphasizing the existence of gaps in perceived value of red palm oil among consumers and producers, and proposing the framework of enhancing red palm oil product performance.